Fertilization and pruning improve vegetative growth and architecture of tropical lowland Borneo Prima Mandarin citrus - Tiara Septirosya; Roedhy Poerwanto; Abdul Qadir (Department of Crop Science, Faculty of Agriculture, Andalas University, 2022)
Vegetative growth of citrus can be increased through a combination of fertilization and pruning. Borneo Prima Mandarin (Citrus reticulata cv Borneo Prima) is a superior local commodity that is grown in lowlands. It has an interesting orange skin, while normally the tropical lowland citrus has a green skin colour. As a new commodity, Borneo Prima Mandarin has to be developed in order to increase production and improve quality. There is no specific cultural practices, so it needs to be developed, especially on fertilizing and pruning. The first experiment aims to observe the plant growth and architecture of plants grown in the orchard. The first factor was the nitrogen fertilization rate (0, 20, 40, 60 g N per tree per application) and the second was pruning (without pruning, open center pruning, hedge pruning). In the second experiment, the plants were applied with the same factors of experiment 1, but were grown on a root observation chamber sized 40 x 20 x 60 cm (length x width x height) which aims to observe the shoot root’s growth and the plant’s biomass. Nitrogen fertilizer had a significant effect to the growth of the Borneo Prima Mandarin, i.e number of shoots and leaves. Twenty grams of nitrogen fertilizer per aplication was efficient to produce new shoots and leaves. Pruning treatments had significant effects towards the plant architecture (i.e reducing plant height, canopy shade projection and canopy length). Open center pruning and hedge pruning made the crown more open which increased the light interception. The shoot grew rapidly two weeks after fertilizing and also pruning. While the root grew rapidly after shoot dormancy.